Veterinary antimicrobial use legislation: A comparative policy analysis of Kenya and Denmark - Mbugua, Simon; Mhone, Amos L.; Morang'a Alexina; Gathura, P.; Onono, J.; Muloi, Dishon M.; Moodley, Arshnee (Elsevier, 2025)
Misuse of antimicrobial in both animal and human health remains a key driver of antimicrobial resistance (AMR). Strengthening policy and regulation framework is essential to promote responsible antimicrobial use (AMU). This study aimed to 1) identify policies and regulations governing AMU in Kenya's veterinary sector and 2) undertake a comparative analysis with Denmark's AMU governance system, widely recognised for its comprehensive approach, to identify potential areas for policy improvement. A desk-based review was conducted to identify relevant AMU policies and legislation in Kenya and Denmark. Data sources included the Food and Agriculture Organisation of the United Nations (FAO) databases (FAOLEX and AMR-LEX), government websites, and publications. Semi-structured interviews with key stakeholders from both countries were used to validate the findings. FAO's framework for analysing AMR-relevant legislation in the food and agriculture sector was used to analyse policies across key areas: veterinary medicinal products, animal health and production, feed legislation, pesticides, water quality, plant health, food safety, environmental health, soil and waste, and institutional coordination. We identified 547 legislative documents in Kenya and 206 in Denmark. The comparative analysis identified several areas where Kenya's policy framework could be further strengthened including enhanced regulation of the use of critically important antimicrobials for humans in animals, creation of sub-national AMU monitoring programs, definition of veterinary prescription benchmarks, and enforcement of restrictions on non-therapeutic use. Further, gaps were identified in policies addressing antimicrobial monitoring in the environment, particularly in soil and waste management, alongside the absence of a dedicated funding mechanism for the country's AMR coordination body and the lack of defined targets for reducing antimicrobial use in animals. The study highlights the importance of continued legislative development in Kenya to enhance AMU governance, particularly in the areas of veterinary oversight, monitoring, and environmental protection. Denmark's experience illustrates the value of integrated legislative approach, which has contributed to measurable reductions in veterinary AMU. Tailoring and strengthening Kenya's regulatory framework, while ensuring coordinated institutional support and sustainable funding, can help align its AMR governance with international standards and contribute to more effective AMR mitigation efforts.